Enhancing Teacher and Student Competence Through CAD-Based Digital Pattern Making Training to Support Fashion Industry 4.0 - Anggraini, Yudhistira; Bahri, Halimul; Widarma, Adi; Annida Damanik, Ulfa; Rahma Dewi, Eka; Ma'ruf Batu Bara, Qothrun Nada (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2025)
The rapid development of Fashion Industry 4.0 requires a digitally skilled workforce, particularly in fashion pattern making using Computer-Aided Design (CAD) software. Nevertheless, initial observations at SMK Negeri 8 Medan indicated that teachers and students are still limited to manual pattern-making practices, which are less relevant to the needs of business and industry. This study aimed to strengthen teacher and student competence through structured CAD-based digital pattern-making training. The training included the introduction of basic CAD tools, practical exercises in digital pattern construction, and pattern printing using a simple plotter. Twenty participants, consisting of teachers and students, were evaluated using pretests and posttests. The findings demonstrated a significant improvement in competence, with the average score increasing from 64.4 (pretest) to 81.1 (posttest). The average N-Gain score was 0.47, categorized as medium, reflecting the effectiveness of the training in enhancing digital skills. The highest improvement was achieved in the accuracy of constructing underarm and side-body lines, while modifications of home-wear patterns showed relatively lower progress. Overall, the program successfully improved the competence of both teachers and students, better preparing them to meet the demands of Fashion Industry 4.0, while also offering a replicable training model for other vocational schools.